Model halal supply chain pada produk kopi - Masruroh, Nikmatul; Fadli, Ahmad; Safitrih, Dina Ayu (STAI Auliaurrasyidin Tembilahan, 2024)
Coffee is inherently a halal product, requiring no further scrutiny regarding its halal status in essence. However, from cultivation to distribution to consumers, there are critical points that necessitate further analysis. This study aims to: (1) explore the halal certification process for coffee products, and (2) develop a halal supply chain model for coffee products. A qualitative approach was employed, utilizing a case study method to provide an in-depth examination of a specific case within a particular location. The research object is Bulan Madu Coffee in Bondowoso Regency, with subjects selected through purposive sampling. Data collection was conducted using observation, interviews, and documentation, and analyzed through Miles and Huberman's flow model technique. Data validity was ensured through source and technique triangulation. The findings reveal that: (1) the halal certification process for Bulan Madu Coffee follows a regular system with tiered halal audits, and (2) the halal supply chain model implemented is a traceability model, which analyzes critical halal points from upstream to downstream. This model assures consumers that, despite being an SME product, Bulan Madu Coffee has obtained official halal certification and is overseen by halal supervisors.